Interleukin-6 Disrupts Synaptic Plasticity and Impairs Tissue Damage Compensation in Multiple Sclerosis. (October 2019) - Stampanoni Bassi, Mario; Iezzi, Ennio; Mori, Francesco; Simonelli, Ilaria; Gilio, Luana; Buttari, Fabio; Sica, Francesco; De Paolis, Nicla; Mandolesi, Georgia; Musella, Alessandra; De Vito, Francesca; Dolcetti, Ettore; et al.
Background: Synaptic plasticity helps in reducing the clinical expression of brain damage and represents a useful mechanism to compensate the negative impact of new brain lesions in multiple sclerosis (MS). Inflammation, altering synaptic plasticity, could negatively influence the disease course in relapsing-remitting MS (RR-MS).Objective: In the present study, we explored whether interleukin (IL)-6, a major proinflammatory cytokine involved in MS pathogenesis, alters synaptic plasticity and affects the ability to compensate for ongoing brain damage.Methods: The effect of IL-6 incubation on long-term potentiation (LTP) induction was explored in vitro, in mice hippocampal slices. We also explored the correlation between the cerebrospinal fluid (CSF) levels of this cytokine and the LTP-like effect induced by the paired associative stimulation (PAS) in a group of RR-MS patients. Finally, we examined the correlation between the CSF levels of IL-6 at the time of diagnosis and the prospective disease activity in a cohort of 150 RR-MS patients.Results: In vitro LTP induction was abolished by IL-6. Consistently, in patients with MS, a negative correlation emerged between IL-6 CSF concentrations and the effect of PAS. In MS patients, longer disease duration before diagnosis was associated with higher IL-6 CSF concentrations. In addition, elevated CSF levels of IL-6 were associated with greater clinical expression of new inflammatory brain lesions, unlike in patients with low or absent IL-6 concentrations, who had a better disease course.Conclusions: IL-6 interfering with synaptic plasticity mechanisms may impair the ability to compensate the clinical manifestation of new brain lesions in RR-MS patients.